2015
DOI: 10.18632/oncoscience.128
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and interpretation of transcriptomic data obtained from extended Warburg effect genes in patients with clear cell renal cell carcinoma

Abstract: BackgroundMany cancers adopt a metabolism that is characterized by the well-known Warburg effect (aerobic glycolysis). Recently, numerous attempts have been made to treat cancer by targeting one or more gene products involved in this pathway without notable success. This work outlines a transcriptomic approach to identify genes that are highly perturbed in clear cell renal cell carcinoma (CCRCC).MethodsWe developed a model of the extended Warburg effect and outlined the model using Cytoscape. Following this, g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 216 publications
(248 reference statements)
1
24
0
Order By: Relevance
“…Indeed, analysis and interpretation of transcriptomic data with the use of Cytoscape network showed highly over-expressed glycolytic genes including HK2, PFKP, ENO2, SLC2A3, SLC16A1, and PDK1 in patients with clear cell renal carcinoma [102]. However, according to this study, some other glycolytic enzymes such as ALDOB, PKLR, PFKFB2, G6PC, PCK1, FBP1, and SUCLG1 were highly down-regulated.…”
Section: Enhancement Of Glycolysismentioning
confidence: 46%
“…Indeed, analysis and interpretation of transcriptomic data with the use of Cytoscape network showed highly over-expressed glycolytic genes including HK2, PFKP, ENO2, SLC2A3, SLC16A1, and PDK1 in patients with clear cell renal carcinoma [102]. However, according to this study, some other glycolytic enzymes such as ALDOB, PKLR, PFKFB2, G6PC, PCK1, FBP1, and SUCLG1 were highly down-regulated.…”
Section: Enhancement Of Glycolysismentioning
confidence: 46%
“… 12 In previous studies, a remarkable decrease in ALDOB was detected in GC, HCC, and clear cell renal cell carcinoma. 11 , 32 , 33 Peng et al identified that the downregulation of ALDOB positively correlated with aggressive features of tumors, such as poor differentiation, a higher grade of TNM stage, earlier tumor recurrence, and shorter 5-year survival. 17 Another study confirmed that lower ALDOB expression in patients was correlated with poor prognosis, and revealed the possible mechanism of ALDOB: ALDOB inhibited HCC metastasis by elevating the expression level of TET1 , a gene acting as a tumor suppressor with the function of promoting DNA demethylation.…”
Section: Discussionmentioning
confidence: 99%
“…The glycolytic switch is an early phenomenon characterized by increased expression of lactate dehydrogenase (LDH, that converts pyruvate into lactate) and inactivation of pyruvate dehydrogenase (PDH, that converts pyruvate into acetyl-CoA for the TCA cycle) [ 40 – 46 ]. The glycolytic switch is thought to be driven by the hypoxic tumor microenvironment through HIF-1α activation, aberrant signaling due to oncogene activation ( e.g ., Ras, PI3K/mTOR, c-Myc), tumor suppressor gene inactivation ( e.g ., p53), or by mutations in the OXPHOS pathway [ 47 , 48 ].…”
Section: Metabolic Adaptive Mechanismsmentioning
confidence: 99%